Karateristik Baja Tulangan Polos Pada Mutu Beton K 175 Tebal Selimut 3 Cm Terbakar Dengan Durasi Yang Berbeda - Ukiman Ukiman; Setio Utomo; Imam Nurhadi; Pentardi Rahardjo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2016)
Concrete is a building material that is inexpensive and easily compacted or made, can meet their needs both in terms of strength and in terms of span length dimensions required. Advances in technology and the improvement of public welfare encourage residential development into a multi-storey building lots (flats) with reinforced concrete products. The rapid development of home stores, or so-called good-story office two (2) or (three) were not followed appropriate equipment for anticipated fire hazard. So sometimes when there is a fire and in addition to material losses also no casualties. Concrete is known material which is resistant to fire when it burns for a long time and high temperatures will be damaged (compressive strength is going down), certainly in reinforced concrete yuga will occur such things, besides the concrete was broken of course steel reinforced also damaged / decrease its tensile strength. Moreover, the reinforcing steel material is heat conducting material and when at certain high tempertures will melt and fuse so liquid. So that the structure of reinforced concrete as a building component when exposed to heat of fire with high temperatures and a long duration will decrease the tensile strength of steel reinforcement will bepengaruh on the stability of the building structure construction. As a result of the reinforced concrete structure with concrete cover thickness of 3 cm if burned by hot embers will decrease the strength of the quality of concrete K 175 if burned to 4 hours more will lose compressive strength of up to 52% and the loss of value of tensile strength in the reinforcing steel to 22%. This assessment is on post-burn conditions (specimen cold conditions). In the burn duration to 8 hours, the compressive strength of concrete K 175, a loss of power by 67% and the loss of tensile strength grades of reinforcing steel at 24.16% (specimen cold onditions or post-combustion testing).